In-session therapist actions for improving client retention in family therapy: Translating empirical research into clinical practice. Issue 2 (3rd April 2018) - McAdams, Charles R.; Foster, Victoria A.; Tuazon, Victor E.; Kooyman, Brian A.; Gonzalez, Edith; Grunhaus, Colleen M. L.; Sheffield, Rebecca L.; Wagner, Nathaniel J.
ABSTRACT: Up to half of clients in psychotherapy do not return after their initial session, and clients in family therapy are more likely than those in individual therapy to terminate after the first session. Recent research has identified six therapist-related conditions in the family therapy session that have influenced client decisions to continue after the first session. This article reports the findings of a review of the professional literature aimed at operationalizing the six therapist-related conditions by identifying specific family therapist actions that can be deliberately applied during initial family therapy sessions to increase the chances that client families will return.